2014
DOI: 10.1002/2013jd020684
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of inertia gravity waves in the troposphere based on the measurements of Wuhan Atmosphere Radio Exploration (WARE) radar

Abstract: Wuhan atmosphere radio exploration (WARE) radar is the first mesosphere-stratosphere-troposphere radar to have become operative in the mainland of China and is dedicated to real-time atmospheric observations. Based on the WARE radar data collected for the period from September 2011 to February 2013, 2666 downward and 1735 upward inertia gravity waves (IGWs) are identified from three-dimensional (3-D) wind fields observed in the troposphere and subsequently analyzed in a statistical manner. Wave characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…The vertical wind has a minimum about −2 m/s in the range 3–4 km at 22:12–22:25 and comparing Fig. 5 a it could be found that echo power of bright band is weak at this moment, which indicates the precipitation particles are not formed in the melting layer but at higher heights because the water vapour is brought from lower to the higher height by the strong warm updraft then condenses into raindrops [21, 23]. Meanwhile, comparing Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The vertical wind has a minimum about −2 m/s in the range 3–4 km at 22:12–22:25 and comparing Fig. 5 a it could be found that echo power of bright band is weak at this moment, which indicates the precipitation particles are not formed in the melting layer but at higher heights because the water vapour is brought from lower to the higher height by the strong warm updraft then condenses into raindrops [21, 23]. Meanwhile, comparing Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic period of 4.7 h is far larger than the buoyancy oscillation period of about 5 min and is one fifth of the inertial oscillation period. In the statistical investigation of IGWs, one tenth of the inertial period is relatively widely chosen as the lower limit of IGWs (Hall et al., 1995; Hamilton, 1991; Hirota & Niki, 1985; Qing et al., 2014; Vincent & Alexander, 2000; Wang et al., 2005; Yoshiki et al., 2004; S. D. Zhang & Yi, 2005, 2007). The observed GW with Ω=5f is regarded as an IGW, which causes some error, whereas the discrepancy may not be very serious, and the hodograph may still help us roughly estimate the horizontal propagation direction of wave.…”
Section: Igw Analysismentioning
confidence: 99%
“…In last few decades, many observational studies improved our understanding of the universal spectra. The characteristics of vertical wavenumber spectrum in the horizontal winds are widely investigated from the troposphere to the mesosphere and lower thermosphere (MLT) based on radiosonde (Guharay et al., 2010; Huang et al., 2018; S. D. Zhang et al., 2017), radar (Dutta et al., 2005; Larsen et al., 1986; Qing et al., 2014), and lidar (Gardner et al., 1998; Senft & Gardner, 1991; Yang et al., 2006) measurements. These observations indicated that the vertical wavenumber spectrum in the horizontal winds has a PSD slope range of about −1.5 to −3.2 in the different atmospheric layers.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the IGWs accurately, the background winds should be appropriately removed from the original wind data. For this purpose, we calculated the background wind by applying a second-order polynomial fitting the vertical profiles of horizontal and vertical winds respectively, following Qing et al (2014a). After subtracting the background wind from the raw data, we could retrieve the zonal, meridional, and vertical components [u, v, w] of the perturbation wind field.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…The phased array of the Wuhan MST radar consists of 24 × 24 three-element Yagi-Uda antennas covering an area of 10000 m 2 . The Wuhan MST radar works at a frequency of 53.8 MHz, a peak power over 170 kW, and a power aperture-area product of 2.0×10 8 Wm 2 (Zhao et al, 2013;Qing et al, 2014aQing et al, , 2014b. In terms of detection height, the radar works in three modes, which are (a) the low mode: 3-10 km; (b) the middle mode: 3-25 km; and (c) the high mode: 60-90 km.…”
Section: Introductionmentioning
confidence: 99%